STUDENT’S PREFERENCE ON CARPOOLING IN UNIVERSITI MALAYA - Yuen Choon Wah; Mohamad Aidil Arbaie Bin Abas (Jurnal Ilmiah Teknik Sipil, 2025)
This study is to understand student’s preference whenever they carpool in university. On top of that, promoting this program to the students is essential to make carpooling a preferable transportation mode. To be able to understand the current situation, questionnaires are distributed around the university. The sample would be random from different faculty, age and place of staying (whether in campus or outside of campus). The questions will be distributed around in the university through WhatsApp since the questions is in Google Form. Student’s main factor they consider whenever they carpool is cost. Daily expenditure of a student can affect one’s daily task. In order to sustain for their whole student life, they tend to plan and keep track of their expenses. Student’s safety can also be an issue especially when it comes to be a passenger of an unknown driver. People can take advantage to the passengers since the passenger cannot do anything to protect themselves. Police can’t really help if the victim cannot identify at least the plate number. Cleanliness of the vehicle is also a concern for vehicle’s owner. Most owners claim that they are unlikely to use their vehicle when it is just washed and cleaned. Suggestion as a rule in policy is made to make as beneficial for both driver and passenger. Method of promoting such method is essential to make students aware for its beneficial for others and environment.